Beta-Alanine Supplementation Improved 10-km Running Time Trial in Physically Active Adults - Santana, Jeferson O.; de Freitas, Marcelo C.; dos Santos, Diana M.; Rossi, Fabrício E.; Lira, Fabio S.; Rosa-Neto, José C.; Caperuto, Erico C. (Frontiers in Physiology, 2018)
The purpose of this study was to verify the effects of β-alanine supplementation on a 10 km running time trial and lactate concentration in physically active adults. Sixteen healthy subjects were divided randomly into two groups: β-alanine (n=8) and placebo group (n=8). The experimental group ingested 5 g/day of β-alanine plus 1 g of resistant starch, and control group ingested 6 g of resistant starch, both for 23 days. Time to complete a 10-km running time trial and lactate concentration following the test were assessed at baseline and post 23 days. The running training program was performed three times per week on nonconsecutive days (Day 1: Running 7 km; Day 2: 6 sprints of 500 meters at maximum speed with two minutes of recovery; Day 3: Running 12 km). The time to complete a 10-km running time trial decreased significantly only for the β-alanine group (Pre= 3441±326.7, Post= 3209±270.5 seconds, p<0.05). When analyzing the delta (Time post minus Time at baseline value) there was a statistically significant difference between the β-alanine versus placebo group (-168.8 ± 156.6 vs -53.60 ± 78.81 seconds, p= 0.007), respectively. In addition, the β-alanine group presented lower blood lactate concentration after the 10-km test (β-alanine: Pre= 8.45±1.94 vs Post= 6.95 ± 2.44 mmol/L; Placebo: Pre= 8.7±3.0 vs Post= 10.8±2.5 mmol/L, p= 0.03). In conclusion, β-alanine supplementation improved the 10-km running time trial and reduced lactate concentration in physically active adults.